2012
DOI: 10.5812/hepatmon.837
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Benefits of Antioxidant Agents in Acute and Chronic Hepatitis

Abstract: ContextOxidative damage due to oxidative stress is the failure of the cell's defense against the deleterious effects of harmful agents by means of its numerous autoprotective mechanisms. oxidative stress is a key impairment induced by various conditions, including atherosclerosis, hypertension, ischemia-reperfusion, hepatitis, pancreatitis, cancer, and neurodegenerative diseases.Evidence AcquisitionOxidative stress is a common pathogenetic mechanism contributing to the initiation and progression of hepatic dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…In addition, antioxidant drugs composed of ebselen (glutathione peroxidase analogue) have been used in early liver damage caused by alcohol. Studies have shown that vitamin E inhibits HBV replication and TGF- β gene expression in a rat model of NASH [68, 69]. …”
Section: Os-related Potential Therapeutic Targetsmentioning
confidence: 99%
“…In addition, antioxidant drugs composed of ebselen (glutathione peroxidase analogue) have been used in early liver damage caused by alcohol. Studies have shown that vitamin E inhibits HBV replication and TGF- β gene expression in a rat model of NASH [68, 69]. …”
Section: Os-related Potential Therapeutic Targetsmentioning
confidence: 99%
“…Previous studies have reported that oxidative stress takes part in pathogenesis of both HCC and CHB 5, 6. Bolukbas et al reported that increased oxidative stress was involved in various forms of HBV infection 7.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the symptoms and pathology of viral diseases are ultimately the result of complex host reactions in addition to direct viral effects, there is a scientific basis for this strategy of viral disease therapy. Clearly, this does not obviate the need for further research to identify a drugs that may specifically interfere with viral replication [40,42,43] . The modulation of major signaling the Nrf2/ARE signaling pathway is triggered at least by five of the HCV viral proteins (core, E1, E2, NS4B, and NS5A).…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…Triple antioxidants therapies have been tested in clinical trials, which include alpha-lipoic acid, silymarin and selenium in order to suppress HCV-induced liver damage, when used together with Vitamins C and E, and in a healthy diet and exercise regime [43,75,76] . Several studies are in favor of a positive control of HCV replication by oxidative stress and to search counteracting this effect.…”
Section: Acetylsalicylic Acidmentioning
confidence: 99%